Comparison of the neurological outcomes and infection rate in surgical and conservative management of compound depressed skull fractures - Shashank Nahar; Pavni Agrawal (Romanian Neurosurgery)
Background: Depressed skull fractures (DSFs) constitute a significant chunk of head injuries. As per level 3 evidence of recent brain trauma foundation guidelines, depressed fracture segments greater than the thickness of the calvaria should undergo operative intervention to prevent infection and to improve neurological outcomes. This study was done to refute the Brain Trauma Foundation guidelines of level 3 evidence by non-surgical management of those depressed skull fractures in which surgical management is indicated, and we aimed to assess and compare the incidences of infection rate and neurological outcomes in patients of surgical and conservative management of depressed skull fractures.